The Implementation Of Statistical Process Control (SPC) Method On Carton Box Production - Rahmawati, Ayu Nova; Shalshabilla, Asyiffa Ananda (Sainteks: Jurnal Sain dan Teknik, 2025)
Due to the era of high industry growth, the packaging industry in Indonesia has to raise the quality of its goods. PT Kartonindo Mega Jaya, a corrugated cardboard supplier company, needs to maintain the quality of their products to ensure that the quality standards are met. The SPC (Statistical process control) method is implemented to control product quality and reduce defect rates. This study uses the SPC method with the attribute control map (p-chart) technique because the data used are the number of product defect products with a non-constant sample size. There are four main problems, namely inappropriate product size (34.5%), skewed image printing (21.8%), imperfect product shape (25%) and uneven coloring (18.7%) with a total of 3,913 units of product defects. The results showed that the quality of cardboard box products at PT Kartonindo Mega Jaya could not be controlled statistically, the control chart showed that there were only 17 data within the control limits, which indicated that quality control was not consistently implemented. The types of deffect and their causes are examined using the Cause Effect Diagram approach.. Based on the observations, the factors that influence the above problems are human factors, machines, methods, environment and materials used.